The Properties of Ethyl Acetate Extract of Frankincense (Styrax benzoin) Using the Maceration Method - Susanti, Nora; Purba, Jamalum; Tambunan, Salsabila (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
This study aims to determine the standardization of ethyl acetate extract of frankincense gum using the maceration method. The method used in this study was to standardize the ethyl acetate extract of frankincense using specific and non-specific parameters. The results of standardization with specific parameters showed that the ethyl acetate extract of frankincense latex was blackish brown in color and had a distinctive odor of frankincense. It contained 86.5% soluble compound in ethanol. The results of standardization with non-specific parameters showed a specific gravity of 0.8213 g/ml and an average moisture content of 1.71%. The chemical components contained are Benzoic acid; Vanillin; transCinnamic acid; Phenol, 2-methoxy-4-propyl-; 2-Propanone, 1-(4) -hydroxy-3-methoxyphenyl)-; Benzoic acid, phenylmethyl ester; (Z)-Cinnamyl benzoate; 2-Propenoic acid, 3-phenyl-,phenylmethyl ester, (E) -; and Cinnamyl cinnamate.